EVALUASI SISTEM ALOKASI AIR PADA MUSIM TANAM (MT-I) TAHUN 2021 DI DAERAH IRIGASI TALAWAAN KABUPATEN MINAHASA UTARA - S. Tombeng; L. Kalesaran; D. Rumambi (COCOS, 2023)
ABSTRACT Based on data from the Ministry of PUPR as stated in the PUPR Ministerial Regulation No. 14 of 2015 concerning Criteria and Status of Irrigation Areas, the area of the Talawaan Meras Irrigation Area (DI) is 1705 Ha, but over time observations in the field show that its functional area is decreasing. who made this research carried out, with the aim of getting an overview and identification of the components of the irrigation system, in order to be able to assess the condition of the air allocation system in the first planting season (MT-I) in 2021 and to know the management system. 2 This research is carried out directly in the field and data collection is carried out using a survey method to selected respondents, and measurement or analysis of variables related to irrigation networks is carried out directly on the research object. Based on the data and information from the research, it can be said that, the condition of the irrigation infrastructure at the research site on the Talawaan irrigation network right from tapping gate 3, starting from dams, primary canals, secondary canals, tertiary canals, sharetapping buildings and sluice gates is still complete. and works well, so that the water discharge allocated at the intake point of tapping door 3 is sufficient so that it can meet the needs of the tertiary plots in the research location. Primary and secondary irrigation networks are still running well, while tertiary irrigation networks are relatively poorly managed due to the inactivity of P3A, so indications of decreasing functional area in the Talawaan Meras Irrigation Area are not proven at the study site, and are thought to occur in other locations. Keywords : Evaluation, Water Allocation, Growing Season.